An Approach to Analyzing Changes in Gene Expression of Non-model Plant Species Grown Under Elevated CO2 and Soil N Levels - Radeke, Leah; Moran, Patrick (My University, 2015)
We are specifically interested in the interactive effects of elevated CO2 and elevated nitrogen levels on the expression of genes involved in nitrogen metabolism and photorespiration as photorespiration is directly affected by CO2 and is linked with nitrogen assimilation and metabolism.
Color poster with text, images, graphs, charts, and photographs.
Keywords: Ecology; Plant genetics; Soil nitrogen; Posters